Cyber Security: The complete guide to cyber threats and protection - David Sutton (BCS Learning & Development Limited, 2022)
Cyber security has never been more essential than it is today, it's not a case of if an attack will happen, but when. This brand new edition covers the various types of cyber threats and explains what you can do to mitigate these risks and keep your data secure. Cyber Security explains the fundamentals of information security, how to shape good organisational security practice, and how to recover effectively should the worst happen. Written in an accessible manner, Cyber Security provides practical guidance and actionable steps to better prepare your workplace and your home alike. This second edition has been updated to reflect the latest threats and vulnerabilities in the IT security landscape, and updates to standards, good practice guides and legislation. • A valuable guide to both current professionals at all levels and those wishing to embark on a cyber security profession • Offers practical guidance and actionable steps for individuals and businesses to protect themselves • Highly accessible and terminology is clearly explained and supported with current, real-world examples